The effect of inorganic solid particles on water and crude oil emulsion stability - Mohd. Hafiz, Mohamed (2009)
Emulsion either water-in-oil or oil-in-water emulsion can be important in almost all stages of upstream activities in petroleum industry nowadays. Crude oil have become an important sources of hydrocarbons in every part of the world which the formation of crude oil emulsion due to high paraffinic compound existed in the crude oil problem in dewatering stage of the crude emulsion. Many studies have been conducted in which to find a source that can stabilize the crude emulsion and how it affected the crude emulsion itself. Emulsion stability is determined by the extend of water resolved in which it is a measurement of the degree of disperse-phase coalescence after the separation process. All particles used were hydrophilic, can stabilized oil-in-water emulsions that are commonly found in refinery emulsions. In order to get better understanding in the effect of inorganic solid particles on the stability of crude oil emulsion, three types of crude oil emulsions were used and three types of inorganic solid particles was studied under various ratios of water/oil and weight percentage of the inorganic solid particles to the emulsions. The result showed that in increasing the weight percentage of the inorganic solid particle in the crude oil, the percent of water resolved is decreased slightly. And it was also observed that Kaolin has the largest stabilization effect in emulsions rather than Iron Oxide and Calcium Hydroxide. Comparing the crude oil used for this study, it is found that Masila crude oil is the most stable crude oil while Dubai and Miri crude oil show less stable properties. This is mainly because of the asphaltene content in the crude oil itself that can affect the stability of water and crude oil emulsion.